PENGARUH LOCUS OF CONTROL DAN DUKUNGAN SOSIAL TERHADAP EFIKASI DIRI ATLET BADMINTON - Amanda, Nicola Kautsar; Adriani, Yufi (Psikologi UHAMKA, 2021)
This research was conducted to determine the effect of locus of control, social support and demographics factors on self-efficacy in badminton athletes. This research used a quantitative approach with multiple regression analysis with the help of SPSS 23 software. The samples consist of 153 badminton athletes were taken using a non-probabilty sampling technique, namely accidental sampling. The data collection instrument that is used in this research was an adaption scale of Indonesian version of General Self Efficacy Scale (GSES), Levenson Internality Powerful others Chance (IPC) Scale, and The Multidimensional Scale of Perceived Social Support (MSPSS). The author tested the validity of the measuring instrument using confirmatory factor analysis with Lisrel 8.80 software. The results showed that there was a significant effect of locus of control, social support and demographics factors on self-efficacy in badminton athletes. The R-Square value which obtained is 0,493. It means that all independent variables have an influence of 49,3% on the dependent variable. As for the regression coefficient value of each independent variable, only internality, family, friend, and significant others who have the influence on self-efficacy in badminton athletes. The author hopes that the results of this research can be reviewed and developed in further research.